Strength characteristics and prediction model of solidified municipal sludge reinforced by dredged silt combined with sodium silicate and polyurethane - Yupeng Cao; Hui Lin; Tong Zong; Xiangbo Xu; Mingdong Li; Xia Bian; Zhiqiang Li (Scientific Reports)
Abstract The treatment and resource utilization of municipal sludge and dredged silt have been rendered urgent by the acceleration of urbanization and stricter environmental protection demands. An effective solution was developed to address the challenges of poor mechanical properties and the difficulty in directly using cement-based materials for municipal sludge treatment. The utilization of dredged silt with high water content served as the foundational skeleton material. Appropriate proportion (0.5:1.0) of sodium silicate, which accelerates cement hardening, and polyurethane, which facilitates chemical bond cooperation, was combined to form SP material, partially replacing cement. Unconfined compressive strength (UCS) tests were subsequently conducted on the solidified municipal sludge. These tests aimed to investigate the influence of the dredged silt mixing ratio, initial water content of dredged silt, and the SP mixing ratio on the strength of the solidified municipal sludge. Furthermore, a strength prediction model was established for solidified municipal sludge, taking into consideration the mixing ratios of dredged silt and SP. The research findings indicate that dredged silt can serve as a skeleton structure for solidified municipal sludge. The UCS of the solidified municipal sludge increases with the increase in the dredged silt mixing ratio, and reaches a maximum value at mixing ratio of 1.0. SP materials can partially replace cement, the appropriate proportion of SP and cement can synergistically improve the strength of solidified municipal sludge, and the optimal SP mixing ratio is 50%. Furthermore, the strength prediction model constructed with independent variables such as dredged silt mixing ratio, curing age, water-to-cement ratio, and SP mixing ratio demonstrates better predictability for the strength development of solidified municipal sludge.